New‐old hemoglobin‐like proteins of symbiotic dinoflagellates. Issue 4 (26th February 2013) - Rosic, Nedeljka N.; Leggat, William; Kaniewska, Paulina; Dove, Sophie; Hoegh‐Guldberg, Ove
Abstract Symbiotic dinoflagellates are unicellular photosynthetic algae that live in mutualistic symbioses with many marine organisms. Within the transcriptome of coral endosymbionts Symbiodinium sp. (type C3), we discovered the sequences of two novel and highly polymorphic hemoglobin‐like genes and proposed their 3D protein structures. At the protein level, four isoforms shared between 87 and 97% sequence identity for Hb‐1 and 78–99% for Hb‐2, whereas between Hb‐1 and Hb‐2 proteins, only 15–21% sequence homology has been preserved. Phylogenetic analyses of the dinoflagellate encoding Hb sequences have revealed a separate evolutionary origin of the discovered globin genes and indicated the possibility of horizontal gene transfer. Transcriptional regulation of the Hb‐like genes was studied in the reef‐building coral Acropora aspera exposed to elevated temperatures (6–7°C above average sea temperature) over a 24‐h period and a 72‐h period, as well as to nutrient stress. Exposure to elevated temperatures resulted in an increased Hb‐1 gene expression of 31% after 72 h only, whereas transcript abundance of the Hb‐2 gene was enhanced by up to 59% by both 1‐day and 3‐day thermal stress conditions. Nutrient stress also increased gene expression of Hb‐2 gene by 70%. Our findings describe the differential expression patterns of two novel Hb genes from symbiotic dinoflagellates and their polymorphic nature. Furthermore, the inducible nature of Hb‐2 gene by both thermal and nutrient stressors indicates a prospective role of this form of hemoglobin in the initial coral–algal responses to changes in environmental conditions. This novel hemoglobin has potential use as a stress biomarker.